Fuzzy logic for regulating the speed of a direct current (DC) motor - Tejada Muñoz, Guillermo (2023)
This study focuses on designing and describing the operation of a fuzzy controller to regulate the speed of a direct current (DC) motor, widely used in spacecraft, defense machinery, robotics, electric trains, electric vehicles, and cranes. The article compares the results of the fuzzy controller with those of a proportional integral derivative (PID) controller, which was tuned using MATLAB tools. Transients of the motor speed curve, such as rise time, settling time, and overshoot, were measured. Regarding transients, the proposed fuzzy controller achieved better results than the PID controller tuned by MATLAB.